Isolation and genetic characterization of Toxoplasma gondii from striped dolphin (Stenella coeruleoalba) from Costa Rica - Dubey, J. P. (2007)
Toxoplasma gondii infection in marine mammals is of interest because of mortality and mode of transmission. It has been suggested that marine mammals become infected with T. gondii oocysts washed from land to the sea. We report the isolation and genetic characterization of viable T. gondii from a striped dolphin (Stenella coeruleoalba), the first time from this host. An adult female dolphin was found stranded on the Pacific Coast of Costa Rica, and the animal died the next day. The dolphin had a high (1:6,400) antibody titer to T. gondii in the modified agglutination test. Severe nonsuppurative meningoencephalomyelitis was found in its brain and spinal cord, but T. gondii was not found in histological sections of the dolphin. Portions of its brain and the heart were bioassayed in mice for the isolation of T. gondii. Viable T. gondii was isolated from the brain, but not from the heart, of the dolphin. A cat fed mice infected with the dolphin isolate (designated TgSdCo1) shed oocysts. Genomic DNA from tachyzoites of this isolate was used for genotyping at 10 genetic loci, including SAG1, SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1, and Apico, and this TgSdCo1 isolate was found to be Type II.